Aplikasi Pembayaran Pajak Kendaraan Bermotor Online Berbasis Web (Studi Kasus Di Samsat Soreang Kab. Bandung) - Ali Mulyawan; Dini Novia (Jurnal Computech & Bisnis (e-Journal), 2016)
The purpose of this study to create an application-based motor vehicle tax calculation web online. Currently the data processing is still done manually which caused some problems and require a long time to make the payment by the taxpayer, so it needs to be made an application that can handle these problems. To achieve these objectives need to be done in the following steps of conducting systems analysis, design and implement applications tally of motor vehicle tax. Through this system is expected to support to facilitate taxpayers in paying taxes on motor vehicles.  Keywords: taxes on motor vehicles; Web-based.